Structure and manufacturing method thereof

JP7638564B2Active Publication Date: 2025-03-04RYUKOKU UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024001099
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-01-09
Publication Date
2025-03-04
Estimated Expiration
2040-03-23

AI Technical Summary

Benefits of technology

【0015】 本発明の構造体は、バナジン酸ビスマスが単斜晶であるため、高い光触媒効果を奏する。また、本発明の製造方法によれば、前記構造体を、実用的に作製することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638564000001
    Figure 0007638564000001
  • Figure 0007638564000002
    Figure 0007638564000002
  • Figure 0007638564000003
    Figure 0007638564000003
Patent Text Reader

Abstract

To provide a structure having a high photocatalyst effect and a method for producing the same.SOLUTION: This invention relates to a structure having monoclinic bismuth vanadate on a substrate. This invention also relates to a method for producing a structure including the steps of: layering a vanadium-containing compound on a substrate; layering bismuth vanadate on the layered vanadium-containing compound, to produce the layered body; and heating the resultant layered body.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a structure having a photocatalytic effect and a method for producing the same. [Background technology]

[0002] The band gap of monoclinic bismuth vanadate (BiVO4) is 2.4 eV (corresponding to a wavelength of approximately 517 nm). Compared to titanium oxide, which utilizes ultraviolet light with a wavelength of 388 nm or less, which corresponds to a band gap of 3.2 eV, it absorbs approximately 3.5 times the amount of solar energy and is therefore expected to be a highly efficient photocatalyst.

[0003] In order to use bismuth vanadate as a visible light responsive photocatalyst, it is necessary to form a thin film on a substrate such as a wall tile. The following methods can be used to form the film. (1) A coating method in which a coating material containing bismuth vanadate, an organic solvent, and a binder is applied to a substrate (for example, Patent Documents 1 and 2) (2) A sputtering method in which a target (bismuth vanadate) is sputtered onto a substrate.

[0004] The coating method has the problem that the binder in the coating hinders the organic environmental pollutants to be decomposed from coming into contact with the bismuth vanadate catalyst, and that the binder itself decomposes and deteriorates due to photocatalytic action. On the other hand, the sputtering method has the problem that the bismuth vanadate does not crystallize, making it difficult to demonstrate photocatalytic effects. When sputtering is performed for about 10 hours, tetragonal crystals are formed, but this is unrealistic from the perspective of practicality. In addition, even after 10 hours, monoclinic crystals with high photocatalytic effects did not appear. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2008-19156 A [Patent Document 2] WO2006 / 064799 specification Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a structure having a high photocatalytic effect and a method for producing the same. [Means for solving the problem]

[0007] The present inventors investigated converting a sputtered film of bismuth vanadate into a monoclinic crystal by heat treating the film. They found that vanadium does not easily adhere to a substrate, and the bismuth vanadate turns into bismuth oxide, making it impossible to form a monoclinic crystal of bismuth vanadate. However, they discovered that if a thin film containing vanadium is formed under the thin film of bismuth vanadate to compensate for the vanadium, the vanadium will diffuse from the thin film during heat treatment, and a monoclinic crystal of bismuth vanadate will be formed on the substrate, thereby completing the present invention.

[0008] That is, the present invention relates to a structure having monoclinic bismuth vanadate grains on a substrate.

[0009] It is preferable that a layer containing vanadium other than bismuth vanadate is provided on a part of the outer periphery of the bismuth vanadate particle.

[0010] The present invention also relates to a method for producing a structure, comprising the steps of: laminating a vanadium-containing compound on a substrate; laminating bismuth vanadate on the laminated vanadium-containing compound to produce a laminate; and heat-treating the obtained laminate.

[0011] In the above-mentioned production method, the method for laminating the vanadium-containing compound is preferably a coating method.

[0012] In the above-mentioned manufacturing method, the method for depositing bismuth vanadate is preferably a sputtering method, a molecular beam epitaxy method, an electron beam deposition method, or a metal-organic chemical vapor deposition method.

[0013] In the above-mentioned production method, the heat treatment time is preferably 1 hour or longer.

[0014] In the above-mentioned manufacturing method, the heat treatment temperature is preferably 600° C. or higher. Effect of the Invention

[0015] The structure of the present invention exhibits a high photocatalytic effect because the bismuth vanadate is a monoclinic crystal. Furthermore, the manufacturing method of the present invention makes it possible to practically manufacture the structure. [Brief description of the drawings]

[0016] [Figure 1] 1A is an electron microscope photograph of the surface of the structure produced in Example 2. FIG. 1B is an electron microscope photograph of bismuth vanadate particles. FIG. 1C is a schematic diagram of the structure of the surface of the structure. [Diagram 2] 1 shows XRD charts of the structure produced in Example 2 and the laminate produced in Comparative Example 5. [Diagram 3] 1 shows XRD charts of the structures produced in Examples 1 to 4. [Figure 4] 1 shows XRD charts of the structures produced in Examples 5 to 8. [Diagram 5] 3 shows XRD charts of the laminates produced in Comparative Examples 1 to 4. [Figure 6] FIG. 13 is a plot of transmittance versus wavelength for methylene blue solutions treated with the structure produced in Example 2 and the laminate produced in Comparative Example 5. [Figure 7] FIG. 1 is a plot of transmittance versus wavelength for methylene blue solutions treated with the structures produced in Examples 1 to 4. [Figure 8] FIG. 1 is a plot of transmittance versus wavelength for methylene blue solutions treated with the structures prepared in Examples 1, 2, and 5 to 8. [Figure 9] FIG. 13 is a plot of transmittance versus wavelength for a methylene blue solution treated for a given time period using the structure produced in Example 8. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The structure of the present invention is characterized in that it has monoclinic bismuth vanadate particles on a substrate. In the laminate, it is preferable that a layer containing vanadium other than bismuth vanadate is provided on a part of the periphery of the bismuth vanadate particles.

[0018] The material of the substrate is not particularly limited, and examples thereof include silicon, glass, quartz glass, metal plate, etc. Among these, silicon and quartz glass are preferable in terms of heat resistance.

[0019] The vanadium in the layer containing vanadium different from bismuth vanadate is not only vanadium itself, but also V2O5, VO2, V2O4, V2O3, and V6O 13 The vanadium-containing thin film is present so as to cover a part of the outer periphery of the bismuth vanadate particle. The film thickness is preferably 1 to 10,000 nm, more preferably 10 to 1,000 nm. If it exceeds 10,000 nm, the transparency becomes poor, and if it is less than 1 nm, the amount of vanadium that diffuses tends to be small.

[0020] The content of vanadium other than bismuth vanadate is preferably 1 to 100,000 parts by mass, more preferably 10 to 10,000 parts by mass, and even more preferably 100 to 1,000 parts by mass, relative to 100 parts by mass of bismuth vanadate. If it exceeds 100,000 parts by mass, vanadium is oversupplied and the transmittance tends to decrease. On the other hand, if it is less than 1 part by mass, vanadium is insufficiently supplied.

[0021] The particle diameter of the bismuth vanadate particles is preferably 10 to 100,000 nm, more preferably 50 to 10,000 nm, and even more preferably 100 to 1,000 nm. If the particle diameter exceeds 100,000 nm, the surface area increases, the transmittance of the sample decreases, and the sample tends to be colored yellow. If the particle diameter is less than 1 nm, the contact area with the substrate decreases, and the sample tends to peel off from the substrate.

[0022] Bismuth vanadate is a monoclinic crystal, but it is not necessary that all the crystals are monoclinic, as long as some of them are monoclinic. The proportion of monoclinic crystals is preferably 50% or more, and more preferably 70% or more. The crystal structure can be identified by X-ray diffraction. The 2θ of the monoclinic crystal is 19, 28.8, 30.5, 34.5, 35.2, and 42.3 degrees. On the other hand, the 2θ of the tetragonal crystal is 18.3, 24.4, 30.7, 32.7, 34.7, 39.5, and 48.4 degrees.

[0023] The structure of the present invention can be widely used as a visible light responsive photocatalyst. Unlike the case of a powdered photocatalyst, it is not necessary to remove the photocatalyst by filtration or the like after purification, and it can be used more easily. For example, it can be applied to a water purification method using visible light, and can be applied to a method for photodecomposing endocrine disrupting substances such as nonylphenol, bisphenol A, and natural estrogen.

[0024] The method for producing a structure of the present invention is characterized by comprising the steps of: laminating a vanadium-containing compound on a substrate; laminating bismuth vanadate on the laminated vanadium-containing compound to produce a laminate; and heat-treating the obtained laminate.

[0025] The substrate may be any of those described above. The vanadium-containing compound may be any of those compounds containing vanadium other than bismuth vanadate, and may be any of those described above.

[0026] The method for depositing a vanadium-containing compound on a substrate is not particularly limited, and examples thereof include coating, sputtering, molecular beam epitaxy (MBE), electron beam (EB), and metalorganic chemical vapor deposition (MOCVD), with coating being preferred in terms of vapor pressure, melting point, and boiling point. Examples of coating methods include bar coating, spin coating, and dipping. Examples of compounds that serve as vanadium sources include V (vanadium), V2O5 (vanadium pentoxide (V)), VO2 (vanadium IV oxide)), V2O3 (vanadium (III) oxide), and V6O 13 (hexavanadium IV, V)), F3VO (vanadium trifluoride oxide (V)), NH4VO3 (ammonium metavanadate), VOCl3 (vanadium oxytrichloride (V)), NaVO3 (sodium metavanadate (V)), KVO3 (potassium vanadate (V)), VCl4 (vanadium tetrachloride IV)), VOSO4 (vanadium oxysulfate), VOCl2 (vanadium oxydichloride IV)), VCl3 (vanadium trichloride (III)), Na3VO4 (sodium vanadate (V)), etc. These compounds can also be used in combination. In addition, the form of the vanadium-containing compound laminated on the substrate is not particularly limited, and examples thereof include thin films, particles, and thin films containing particles.

[0027] The thickness of the layer of the vanadium-containing compound is preferably 1 to 10,000 nm, more preferably 10 to 1,000 nm. If it exceeds 10,000 nm, the transparency deteriorates, and if it is less than 1 nm, the amount of vanadium that diffuses tends to be small.

[0028] It is preferable to laminate the vanadium-containing compound on the substrate and then calcinate it. The calcination temperature is preferably 300°C or higher, more preferably 500°C or higher, and even more preferably 600°C or higher. If the temperature is lower than 300°C, the bismuth vanadate may not become a monoclinic crystal. The upper limit of the calcination temperature is not particularly limited, but is preferably 1000°C or lower. The atmosphere during calcination is not particularly limited, but is preferably performed in air.

[0029] The firing time depends on the firing temperature, but is preferably 0.5 hours or more, more preferably 1 hour or more, and even more preferably 2 hours or more. If it is less than 0.5 hours, the bismuth vanadate may not become a monoclinic crystal. The upper limit of the firing time is not particularly limited, but it is preferably 15 hours or less.

[0030] The lamination method of bismuth vanadate is not particularly limited, and examples thereof include sputtering, coating, MBE, EB, MOCVD, etc., but sputtering is preferred in terms of production costs. Also, before laminating bismuth vanadate, fine particles containing bismuth vanadate may be applied, and then bismuth vanadate may be laminated.

[0031] In the sputtering method, the substrate can also be heated. The heating temperature is preferably 50° C. or higher, more preferably 100° C. or higher, and even more preferably 300° C. or higher. If the temperature is less than 50° C., bismuth vanadate tends to become a tetragonal crystal. The upper limit of the heating temperature is not particularly limited, but it is preferably 500° C. or lower.

[0032] The thickness of the layer containing bismuth vanadate is preferably 1 to 10,000 nm, and more preferably 10 to 1,000 nm. If it exceeds 10,000 nm, the layer becomes opaque, and if it is less than 1 nm, the bismuth vanadate tends to be tetragonal instead of monoclinic. The layer containing bismuth vanadate may be a layer containing bismuth vanadate containing fine particles.

[0033] In the thin film produced by the sputtering method, bismuth vanadate is amorphous, but can be crystallized into monoclinic crystals by heat treatment. Furthermore, the bismuth vanadate, which was originally a thin film, changes in shape to particles by heat treatment. Here, the thin layer containing vanadium different from bismuth vanadate that was present in the layer below the bismuth vanadate also changes in shape so as to cover part of the outer periphery of the bismuth vanadate particles. Here, the remaining thin film containing vanadium that did not cover the outer periphery of the bismuth vanadate particles may become needle-shaped crystals.

[0034] The heat treatment temperature is preferably 600° C. or higher, more preferably 700° C. or higher. If the temperature is lower than 600° C., bismuth vanadate tends to become a tetragonal crystal. The upper limit of the heat treatment temperature is not particularly limited, but is preferably 1000° C. or lower. The atmosphere during firing is not particularly limited, but it is preferably performed in air.

[0035] The heat treatment time depends on the heat treatment temperature, but is preferably 1 hour or more, more preferably 3 hours or more. If it is less than 1 hour, the bismuth vanadate may not become a monoclinic crystal. There is no particular upper limit to the heat treatment time, but it is preferably 10 hours or less. EXAMPLES

[0036] Examples of the present invention will be described below, but the present invention is not limited to the following examples.

[0037] Comparative Examples 1 to 4 A 1.5cm x 1.5cm silicon substrate was irradiated with UV light for 20 minutes to clean the substrate. While the substrate temperature was heated to 200°C, a BiVO4 film was formed by sputtering to produce a laminate. The sputtering conditions were as follows: reactive gas: Ar, flow rate: 2.5sccm, pressure: 1.0Pa, power: 50W, film formation time: 90 minutes. The thickness of the bismuth vanadate thin film was 100nm.

[0038] The produced laminate was heat-treated at 600° C. for 0.5, 1, 1.5 or 10 hours to produce laminates of Comparative Examples 1 to 4, respectively.

[0039] Comparative Example 5 A 1.5cm x 1.5cm silicon substrate was irradiated with UV light for 20 minutes and cleaned. 30μL of a 2% butyl acetate solution of V2O5 was dropped onto the substrate, spin-coated at 1000rpm for 10 seconds and 2000rpm for 20 seconds, and then baked at 500℃ for 3 hours to form a V2O5 thin film on the silicon substrate. The thickness of the V2O5 thin film was 100nm.

[0040] While heating the substrate temperature to 200 °C, BiVO4 was deposited by sputtering to fabricate a structure. The sputtering conditions were as follows: reaction gas: Ar, flow rate: 2.5 sccm, pressure: 1.0 Pa, power: 50 W, film deposition time: 90 minutes. The film thickness of the bismuth vanadate thin film was 100 nm.

[0041] Examples 1 to 4 The laminate fabricated in Comparative Example 5 was heat-treated at 600 °C for 1, 2, 3, or 4 hours to fabricate the structures of Examples 1 to 4, respectively.

[0042] Examples 5 to 6 The laminate fabricated in Comparative Example 5 was heat-treated at 500 °C for 1 or 2 hours to fabricate the structures of Examples 5 to 6, respectively.

[0043] Examples 7 to 8 The laminate fabricated in Comparative Example 5 was heat-treated at 700 °C for 1 or 2 hours to fabricate the structures of Examples 7 to 8, respectively.

[0044] Figure 1 shows an electron micrograph of the surface of the structure fabricated in Example 2. As shown in (a), it can be seen that innumerable particles exist on the surface of the substrate. The average particle diameter of the bismuth vanadate particles was 150 nm. This particle diameter varies depending on the thickness of the thin film, the heat treatment temperature, and the heat treatment time during firing. Note that the average particle diameter of the bismuth vanadate particles of the structure fabricated in Example 8 was 730 nm. (b) shows a photograph of one particle after observation with a transmission electron microscope (TEM) and elemental analysis by EDX. It can be seen that a part of the bismuth vanadate particles on the substrate side is covered with vanadium oxide (V x O y , where x and y are integers). (c) shows the formation scheme of the structure of the present invention. It is considered that by heat-treating the laminate, the thin film of bismuth vanadate changes into monoclinic crystal particles.

[0045] <X-ray Diffraction> X-ray diffraction was measured using an XRD measuring device (Rigaku Corporation RINT2500V) for the laminate produced in Comparative Example 5 and the structure produced in Example 2. Figure 2 shows the XRD chart. In the laminate of Comparative Example 5, BiVO4 was a tetragonal crystal, and no monoclinic crystals were present. On the other hand, in the structure of Example 2, monoclinic crystals were present in the BiVO4 thin film.

[0046] FIG. 3 shows the X-ray diffraction charts of the structures of Examples 1 to 4, and FIG. 4 shows the X-ray diffraction charts of the structures of Examples 5 to 8. Monoclinic crystals were present in the BiVO4 thin film. It can be seen that, although monoclinic crystals are formed even in a heat treatment time of 1 hour, 2 hours or more is preferable. On the other hand, it was found that, in terms of the heat treatment temperature, monoclinic crystals are sufficiently formed even in 1 hour at 700°C.

[0047] 5 shows X-ray diffraction charts of the laminates of Comparative Examples 1 to 4. Even after heat treatment, only tetragonal crystals appeared, and no monoclinic crystals appeared.

[0048] <Photocatalytic effect> The laminate produced in Comparative Example 5 or the structure produced in Example 2 and an aqueous solution containing 3000 μL (0.1 mM) of methylene blue were placed in a plastic container, and while stirring, the solution was irradiated with visible light (wavelength 100 to 1400 nm) for 60 minutes using a solar simulator device (XES-301S+EL-100, manufactured by Minaga Electric Manufacturing Co., Ltd.). After irradiation, the solution was centrifuged at a rotation speed of 13000 rpm and an operating time of 30 minutes. 300 μL of the obtained solution was placed in a quartz cell, and the transmittance was measured using a spectrophotometer (manufactured by Otsuka Electronics Co., Ltd.).

[0049] 6 shows a plot of the transmittance as a function of wavelength for the treatment solution obtained by treating the laminate produced in Comparative Example 5 or the structure produced in Example 2 for 1 hour. Compared to the laminate produced in Comparative Example 5, the structure produced in Example 2 had a higher transmittance in the visible light region, particularly in the regions of 350 to 550 nm and 700 to 800 nm, indicating a high visible light catalytic effect.

[0050] Fig. 7 shows a plot of transmittance against wavelength for the treatment solution treated for 1 hour using the structures prepared in Examples 1 to 4. Fig. 8 shows a plot of transmittance against wavelength for the treatment solution treated for 1 hour using the structures prepared in Examples 1, 2, and 5 to 8. It can be seen that structures with many monoclinic crystals in the BiVO4 thin film have high methylene blue decomposition ability and high photocatalytic activity.

[0051] 9 shows a plot of transmittance as a function of wavelength for the treatment solution after 7 to 10 hours of treatment using the structure produced in Example 8. It can be seen that the methylene blue is almost completely decomposed by the 10-hour treatment. [Industrial Applicability]

[0052] INDUSTRIAL APPLICABILITY The present invention makes it possible to easily prepare a structure having monoclinic crystals with high photocatalytic effect, and therefore is applicable to various applications utilizing the photocatalytic effect.

Claims

[Claim 1] A structure having monoclinic bismuth vanadate particles on a substrate, a structure having a layer containing a compound containing vanadium on at least a portion of the outer periphery of a bismuth vanadate particle on the substrate side of the particle, the structure not containing tin oxide and the binder of the particle, The vanadium-containing compound is V 2 O 5 (Vanadium (V) pentoxide), VO 2 (Vanadium (IV) oxide), V 2 O 3 (vanadium(III) oxide), or V 6 O 13 (Vanadium(IV,V) oxide).

Citation Information

Patent Citations

  • Preparation method of V2O5 / BiVO4 (vanadium pentoxide / bismuth vanadium oxide) nanorod composite photocatalyst

    CN103908960A

  • Photocatalyst compound powder having visible light responsiveness

    JP2004202335A

  • BiVO4 COLLOID DISPERSION AND METHOD OF MANUFACTURING THE SAME

    JP2008019156A

  • Composite metal oxide photocatalyst exhibiting responsibility to visible light

    WO2006064799A1

  • Bismuth-vanadate-laminate manufacturing method and bismuth-vanadate laminate

    WO2014136783A1